The epidemiology of hospital inpatient exposure to SARS-CoV-2: A cohort study. Issue 3 (September 2021) - Wenlock, Rhys D.; Tausan, Matija; Stoyle, George; Hendron, Holly; Buchanan, Oscar; Tait, Zachary; Whittle, Bethany; McInerney, Samuel; Blackaby, Jessica; Davies, Andrew; Still, Martin; Sargent, Catherine
Summary: Background: Exposure to SARS-CoV-2 was widespread in hospitals during 2020. The risk of infection after in-hospital exposure has not yet been quantified and effective strategies to prevent it remain unclear. Methods: All incidences of patient-to-patient exposure to SARS-CoV-2 on non-COVID wards between October and December 2020 at a UK hospital trust were identified. Patient contacts were traced, and data collected on SARS-CoV-2 testing, symptoms, and outcomes. Factors associated with acquiring infection and mortality were investigated. Results: Of 575 patients exposed, 118 (19.5%) tested positive within 14 days of their exposure, with secondary attack rates (SAR) ranging from 0 to 72%. 68.6% (81/118) of secondary cases had not been in the same bay as the index case. For exposed patients, sharing a bay with the index case and having spent longer on the ward with them were associated with acquiring infection (ORs of 3.8, 95% CI: 1.89, 7.74, and 1.08, 95% CI: 1.01, 1.15 respectively). 71% of secondary cases tested positive while asymptomatic and 94.6% had tested negative earlier in their admission. Conclusions: This is the first study to describe the outcomes of a cohort of patients exposed to COVID-19 in hospital. Exposure to COVID-19 in hospital commonly leads to transmission that is not confined to the index case's bay. This study confirms that asymptomatic testing is important and suggests that an increased frequency of testing may be beneficial. Moreover, we provide factors that can be used to identify the contacts at the greatest risk of acquiring infection.